Digital Technology Empowerment of the Integration of Cultural Tourism and Health Care Industries in Qingyuan City: Dilemmas and Solutions - Liu, Feng (Asia Pacific Economic and Management Review, 2025)
This paper uses Qingyuan City as a case study to explore the challenges and solutions of digital technology - driven integration of cultural tourism and health care industries. Research reveals that Qingyuan’s cultural tourism and health care industry faces several challenges in digital transformation, including poor adaptability of technology to industry scenarios, lack of data sharing mechanisms, difficult coordination of interests among stakeholders, and a shortage of versatile talents. Through theoretical and empirical analysis, the following solutions are proposed: deeply exploring cultural connotations to create unique integrated brands, strengthening talent support to build a multi - level talent system, promoting data sharing to break down information silos, and encouraging multi - party coordination to form an industrial ecosystem community. The study emphasizes that a multi - stakeholder coordination mechanism involving government leadership, enterprise cooperation, and the linkage of universities and research institutions is needed to solve problems such as the disconnection between technology and resources and inefficient data circulation, so as to achieve high - quality integrated development of the industry under digital technology empowerment. This paper provides theoretical references and practical strategies for the digital transformation of cultural tourism and health care industries in Qingyuan City and similar regions, helping to achieve the sustainable transformation of "green waters and green mountains" into "golden and silver mountains."